Skirtboarder Net-a-Narratives: A Socio-Cultural Analysis of a Women's Skateboarding Blog - MacKay, Stephanie (Université d'Ottawa / University of Ottawa, 2012)
This dissertation examines: (a) the discourses of femininity circulating on a female skateboarding blog produced by the Skirtboarders (a group of women skateboarders based in Montréal, Canada); (b) the ways in which the Skirtboarders use Internet blogging (which I label “community media”) to contest (sexist) dominant discursive constructions of sportswomen deployed in mainstream and alternative media; and (c) the ways in which users read and make sense of the Skirtboarders’ blog. For this project, I collected 262 blog posts, including 1128 associated comments, conducted semi-structured interviews with eight Skirtboarders and four users of the blog and incorporated some observational notes. This information was then subjected to discourse analysis informed by the theoretical perspectives of Michel Foucault. This research makes a significant contribution to a growing body of literature in the sociology of sport exploring media (re)presentations of bodies, especially women’s bodies, and lifestyle sports because it is one of the rare studies that goes beyond doing an analysis of media texts – it also uncovers the intentions of the producers of the texts and, in addition, examines the effects of the media discourses for audiences (herein referred to as users). My findings reveal that the Skirtboarders offer something different than mainstream and alternative skateboarding media (re)presentations (i.e., I examined what narratives the Skirtboarders produce about themselves to understand how they appropriate, accommodate or resist gender discourses). The women who produced the blog consciously and purposely challenged dominant discursive fragments. Although users considered the blog inspirational for promoting female skateboarding, they had diverse readings of the Skirtboarders’ attempts to reflexively start a “movement” and, in doing so, construct and circulate a collective identity. I therefore suggest that the Skirtboarders’ blog is one of many political tools and strategies required to change the landscape of the global female skateboarding world. Ultimately, I argue that the Internet is a space where women can have access to predominantly masculine sport and create more fluid definitions of sporting femininity. It provides women with opportunities to control their own (re)presentations, which will challenge male dominated institutions such as mainstream and alternative media organizations.

Cette dissertation étudie : a) les discours sur la féminité qui circulent sur le blogue des Skirtboarders (un groupe de femmes planchistes de Montréal, Canada); b) comment les Skirtboarders utilisent le blogue (que je nomme « média communautaire ») pour contester les discours dominants (sexistes) sur le corps sportif féminin déployées dans le mass média et les média alternatifs; et c) comment les utilisatrices interprètent et accordent un sens au blogue des Skirtboarders. Pour ce projet : j’ai recueillis 262 articles de forum sur le blogue, incluant les 1128 commentaires; effectué des entrevues semi-dirigées avec huit Skirtboarders et quatre utilisatrices du blogue; incorporé des notes d’observation. Ces informations ont ensuite été soumises à une analyse du discours inspirée de la perspective théorique de Michel Foucault. Cette recherche apporte une contribution importante à une littérature croissante en sociologie du sport explorant les (re)présentations du corps, spécialement les corps féminins, et les sports alternatifs; car il s’agit d’une des rares études qui s’aventure au-delà de l’analyse des textes médiatiques. Elle porte aussi sur les intentions des productrices des textes et examine en plus les effets des discours médiatiques sur l’auditoire (c’est-à-dire les utilisatrices). Mes résultats révèlent que les Skirtboarders offrent un contenu qui diffère des (re)présentations du skateboarding dans le mass média et les média alternatifs (par ex., j’ai examiné quels récits les Skirtboarders produisent à propos d’elles-mêmes pour comprendre comment elles s’approprient, s’accommodent ou résistent aux discours sur le genre). Les femmes qui produisent le blogue contestent consciemment et délibérément les fragments discursifs dominants. Quoique les utilisatrices considèrent le blogue inspirant pour la promotion du skateboarding auprès des femmes, elles offrent diverses lectures de la tentative réflexive des Skirtboarders d’initier un «mouvement » et, en ce faisant, de construire et de propager une identité collective. Je suggère donc que le blogue des Skirtboarders est un parmi plusieurs outils politiques et stratégiques requis pour changer le paysage de la scène mondiale des femmes planchistes. Ultimement, j’avance que l’Internet est un espace où les femmes peuvent avoir accès au sport dominé par les hommes et créer des définitions fluides de la féminité sportive. L’Internet offre des occasions aux femmes de contrôler leurs propres (re)présentations, lesquelles contesteront les institutions majoritairement masculines telles que les organisations de mass média et de média alternatifs.
Keywords: Internet; Gender; Skateboarding; Blog; Skirtboarders; Discourse